2016
DOI: 10.1038/eye.2016.287
|View full text |Cite
|
Sign up to set email alerts
|

The gene polymorphisms of IL-8(-251T/A) and IP-10(-1596C/T) are associated with susceptibility and progression of type 2 diabetic retinopathy in northern Chinese population

Abstract: PurposeThe aim of the present study is to investigate the association of the polymorphism of two genes in CXC chemokine family, interleukin-8 (IL-8) and interferon-inducible protein 10 (IP-10), with both susceptibility and progression of DR in T2D population of northern China.Patients and methodsA total of 1043 eligible type 2 diabetic patients from Heilongjiang of northern China were recruited for this study. They were grouped into: with diabetic retinopathy (DR, 528 cases) and without diabetic retinopathy (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…Dong et al [ 69 ] investigated a monocyte chemoattractant protein-1 ( MCP1 ) polymorphism in an Asian DM cohort, and while they observed a significant association with overall DR risk and proliferative DR, they found no association with severity of DME (mildDME = 207, moderateDME = 173, severeDME = 66). Another study by Dong et al [ 70 ] using the same cohort of patients as above [ 69 ], analyzed an association between DR susceptibility and polymorphisms in the CXC chemokine family genes, interleukin 8 ( IL8 or CXCL8 ; -251T>A) and interferon gamma-induced protein 10 ( IP10 or CXCL10 ; -1596C>T) but failed to observe a significant association in a subgroup analysis of DME patients. Finally, Upadhyay et al [ 71 ] studied the association between the sarcolemma-associated protein ( SLMAP ) gene polymorphism, rs17058639, and DR risk.…”
Section: Candidate Genesmentioning
confidence: 99%
“…Dong et al [ 69 ] investigated a monocyte chemoattractant protein-1 ( MCP1 ) polymorphism in an Asian DM cohort, and while they observed a significant association with overall DR risk and proliferative DR, they found no association with severity of DME (mildDME = 207, moderateDME = 173, severeDME = 66). Another study by Dong et al [ 70 ] using the same cohort of patients as above [ 69 ], analyzed an association between DR susceptibility and polymorphisms in the CXC chemokine family genes, interleukin 8 ( IL8 or CXCL8 ; -251T>A) and interferon gamma-induced protein 10 ( IP10 or CXCL10 ; -1596C>T) but failed to observe a significant association in a subgroup analysis of DME patients. Finally, Upadhyay et al [ 71 ] studied the association between the sarcolemma-associated protein ( SLMAP ) gene polymorphism, rs17058639, and DR risk.…”
Section: Candidate Genesmentioning
confidence: 99%
“…We are inclined to consider that at the 1 st stage of developing DRP hypertriglyceridemia takes part in the formation of endothelial dysfunction and provides idiosyncratic metabolic "hit" on rheological properties of blood and endothelium of vessels, contributing to the realization of the influence from such markers of endothelial damage and low-gradual inflammation as interleukin-8 [5,13], inhibitor of activator of plasminogen-1 [3], vascular cell adhesion molecule type 1 [7], which are actively produced in the body in case of obesity. Hypercholesterolemia and dyslipidemia (by cholesterol LDLP), seemingly may lead to further progression of endothelial dysfunction by the type of the "second wave" at later stages of DRP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus prophylaxis of complication of diabetes mellitus (DM) should include further examination of other modifying or non-modifying risk factors. Contemporary references also testify to the importance of other factors including obstructive sleep apnea, nonalcoholic fatty liver disease, level of prolactin, homocysteine and hormones of adipose tissue of blood serum [1, 2, 9-12, 16, 17], genetic factors and endothelial dysfunction in development of DRP [5,13]. Considering the fact that the relative contribution of different factors to the risk of developing retinopathy remains uncertain, the search and study for new risk factors of development and progression of DRP and their modifying influence on components of the metabolic syndrome (MS) at T2DM remain actual.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the rate of progression to vision-threatening retinopathy and particularly in the response to treatment was noted from the onset of clinical and epidemiological studies in diabetic patients and has been attributed to the effect of genetic predisposition together with systemic and socioeconomic factors. Single-nucleotide polymorphisms [58][59][60] and genome-wide associations [61][62][63] have been investigated in patients with proliferative disease and macular edema, and the results so far are inconclusive mainly due to the size of the samples and the Diabetic Retinopathy and Blindness: An Epidemiological Overview DOI: http://dx.doi.org/10.5772/intechopen.88756 inclusion of cases with coexisting proliferations and edema in the cohorts. Detailed assessment in the polymorphisms of the VEGF gene revealed that some of them are related to higher susceptibility to severe retinopathy, but not to the outcome of ranibizumab intravitreal injections [64] in contrast to an earlier report on the response to bevacizumab [65].…”
Section: Progression To Vision-threatening Retinopathymentioning
confidence: 99%